Agricultural Development and Sustainable Intensification - Merrey, Douglas J.; Mondal, Manoranjan K.; Hoanh, Chu Thai; Humphreys, Elizabeth; Dao, Nga (Routledge, 2018)
The livelihoods of people living in coastal deltas, especially in poor tropical countries, are being undermined by multiple insidious trends. Historically, these deltas have attracted large numbers of people, leading to high population densities, because they offer a wide range of ecosystem services. Tropical deltas are characterized by a combination of highly fertile land, multiple marine and freshwater resources, and rich biodiversity. Deltas are often the “breadbaskets” or “rice bowls” of the nations or regions where they are located: examples are the Nile, Irrawaddy, Mississippi and the Cauvery, as well as the Ganges and Mekong river deltas. However, deltas around the world are facing growing threats to their integrity and productivity. The origins of these threats are both anthropogenic and natural, and include the impacts of growing urbanization; agricultural intensication; anthropogenic alterations of ow paths and ood plains; upstream water consumption and pollution; over-extraction of groundwater; trapping of sediments; climate change; sea-level rise whose effects are amplied by sinking land levels and sedimentation of river beds; and extreme events such as river ooding and tidal surges (Renaud et al., 2013).